Organocatalytic asymmetric addition of malonates to unsaturated 1,4-diketones - Žari, Sergei; Kailas, Tiiu; Kudrjashova, Marina; Öeren, Mario; Järving, Ivar; Tamm, Toomas; Lopp, Margus; Kanger, Tõnis (Beilstein Journal of Organic Chemistry, 2012)
The organocatalytic Michael addition of malonates to symmetric unsaturated 1,4-diketones catalyzed by thiourea and squaramide derivatives with Cinchona alkaloids afforded the formation of a new C–C bond in high yields (up to 98%) and enantiomeric purities (up to 93%). The absolute configuration of the product was suggested from comparison of the experimental and calculated VCD spectra of the reaction product 3a.
Keywords: Michael addition; non-covalent catalysis; organocatalysis; squaramide; thiourea